The Philippines: Shadow WTO Agricultural Domestic Support Notifications - Cororaton, Caesar B. (International Food Policy Research Institute, 2008)
The objective of this paper is to review the agricultural trade and domestic policies of the Philippines and to provide an assessment of the types and levels of domestic support relative to the rules of the World Trade Organization (WTO). Changes in trade protection and support in the Philippines, including tariff structure, quantitative restrictions, and domestic support, are discussed and analyzed. The paper also discusses the pattern of public expenditure on agriculture in the Philippines, including major agricultural productivity-enhancing programs. The present structure of protection and support favors the agricultural sector. Trade protection is higher in agriculture relative to manufacturing. There is a quantitative restriction on rice imports and a tariff rate quota in several agricultural commodities. The green box payments and the special and differential treatment constitute the major domestic support for agriculture. These support payments are relatively substantial and will continue to be sizable in the future to support the government’s food sufficiency policy. However, the trade-distorting market price support for rice and corn is significantly below the de minimis limit that applies to the Philippines under the WTO Uruguay Round Agreement on Agriculture.